The Potential of Butterflies in Tourism Diversification Product: Case Study at Coban Rais Waterfall, Batu, East Java - Agung Sih Kurnianto; Imti Yazil Wafa; Faldy Alifianto; Nia Kurniawan (Journal of Indonesian Tourism and Development Studies, 2016)
The diversity of Butterfly in Coban Rais is one of the potential resources for tourism product diversification and development. The aims of this paper are to determine the magnitude of the butterfly potential as a form of tourism products diversification and development in a sustainable tourism industry. There are 107 species of butterfly that come from six families was found in Coban Rais waterfall. Some species have a very large population in a specified activity, such as mud-puddling and mating. Udara akasa has the highest potential to make colony and Cyrestis lutea is a species that have the potential as a major attraction in the mud-puddling activity. Sector 3, the location of riparian with sand and gravel, is the site of the largest butterfly visits. The dry season is the highlight of a butterfly visit in Coban Rais. Development of human resources is important for the tourism products diversification in Coban Rais, i.e. the butterflies observer and visitors services. We recommend establishing a breeding center for butterfly population recovery and educational goals for visitors.Keywords: butterflies, Coban Rais, product diversification.